Territorial approach – the new role of space in socio-economic development - Łuczyszyn, Andrzej; Papież, Patrycja (Podejście terytorialne – nowa rola przestrzeni w rozwoju społeczno-gospodarczym, 2024)
Aim: The aim of the article is to provide a theoretical analysis of the concepts of territory, space, and region in the context of the emerging paradigm of territorially oriented development. A secondary objective is to draw attention to the changing conditions under which contemporary socio-economic realities unfold within the framework of territorial economic cohesion. Methodology: The research method applied is primarily descriptive, involving both a narrative approach and an analysis of the relevant literature. Results: The results obtained have led, among other things, to conclusions emphasizing the necessity of adopting community based (coalition-oriented) approaches in order to make stronger use of creative resources. Implications and recommendations: The authors point to the urgent need to seek new methods and concepts that strengthen socio-economic spaces and enable the monitoring of economic interactions taking place within them. Originality/value: The cognitive value of the article lies primarily in drawing attention to the processes that induce the formation of specific structures of socio-economic development.
Biblioteka Regionalisty = Regional Journal, 2024, Nr 24, s. 142-150
Keywords: territory; territorialisation; space; terytorium; terytorializacja; przestrzeń